2007
DOI: 10.1038/nrm2180
|View full text |Cite
|
Sign up to set email alerts
|

Centrosome biogenesis and function: centrosomics brings new understanding

Abstract: Centrosomes, which were first described in the late 19th century, are found in most animal cells and undergo duplication once every cell cycle so that their number remains stable, like the genetic material of a cell. However, their function and regulation have remained elusive and controversial. Only recently has some understanding of these fundamental aspects of centrosome function and biogenesis been gained through the concerted application of genomics and proteomics, which we term 'centrosomics'. The identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
464
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 506 publications
(472 citation statements)
references
References 147 publications
4
464
1
3
Order By: Relevance
“…Centrosomes are well-known for their role in promoting timely separation of mitotic chromosomes, but are also emerging as potential hubs for cell signaling components, particularly those that rely on the ubiquitin-proteasome system (UPS). 1,2 Consistent with as yet unidentified roles in signaling and proteostasis, we recently found that a C. elegans transcriptional co-activator, the b-catenin SYS-1, is negatively regulated in a cell-cycle dependent manner by localizing to centrosomes during mitosis. 3 Here, we review additional studies that suggest an intriguing role for the centrosome as a physical scaffold for concentrating protein degradation and associated regulatory events during cell signaling.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Centrosomes are well-known for their role in promoting timely separation of mitotic chromosomes, but are also emerging as potential hubs for cell signaling components, particularly those that rely on the ubiquitin-proteasome system (UPS). 1,2 Consistent with as yet unidentified roles in signaling and proteostasis, we recently found that a C. elegans transcriptional co-activator, the b-catenin SYS-1, is negatively regulated in a cell-cycle dependent manner by localizing to centrosomes during mitosis. 3 Here, we review additional studies that suggest an intriguing role for the centrosome as a physical scaffold for concentrating protein degradation and associated regulatory events during cell signaling.…”
Section: Introductionmentioning
confidence: 96%
“…It is composed of 2 centrioles -bilaterally symmetric cylindrical appendages made of short microtubule triplets -surrounded by a pericentriolar material (PCM) -a proteinaceous matrix composed of microtubule-anchoring g-tubulin ring complexes (g-TuRCs), filamentous scaffolds, and various mitotic regulators. 1,4 Centrosomes are highly dynamic non-membranebound organelles whose composition, activity, and behavior can be ultimately controlled by a number of different upstream intracellular cues such as cell cycle status and cell stress. 5,6 Given the centrosome's long-standing, canonical role as a microtubule-organizing center, proteomic analysis of purified centrosomes identify a surprisingly broad list of centrosomal proteins whose functional characterization resist -with even the most generous speculation -placement into any category even tangentially related to microtubule behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In most differentiated cell types, centrioles transform into basal bodies, membrane-embedded centrioles that template cilium and flagellum axoneme assembly. The requirement of cilia and flagella for many developmental and physiological processes, together with the growing list of human diseases that result from defects in basal bodies and cilia (Badano et al, 2006;Bisgrove and Yost, 2006;Bettencourt-Dias and Glover, 2007;Fliegauf et al, 2007;Marshall, 2008), drives the need to understand the basic processes involved in centriole, basal body, cilium assembly, and motility.…”
Section: Introductionmentioning
confidence: 99%
“…In most differentiated cell types, centrioles transform into basal bodies, membrane-embedded centrioles that template cilium and flagellum axoneme assembly. The requirement of cilia and flagella for many developmental and physiological processes, together with the growing list of human diseases that result from defects in basal bodies and cilia (Badano et al, 2006;Bisgrove and Yost, 2006;Bettencourt-Dias and Glover, 2007;Fliegauf et al, 2007;Marshall, 2008), drives the need to understand the basic processes involved in centriole, basal body, cilium assembly, and motility.In Drosophila several approaches have identified evolutionarily conserved centriole proteins required for centriole biogenesis including Sak, Sas4, Sas6, Ana1, Ana2, and Asterless (Bettencourt-Dias et al, 2005;Basto et al, 2006;Goshima et al, 2007;Rodrigues-Martins et al, 2007;Blachon et al, 2008). In flies, mutations in these genes abolish centrosome and cilium/flagellum assembly (except mutations in ana1 and ana2, which have not been described yet).…”
mentioning
confidence: 99%
“…Centrioles are complex cylindrical-shaped structures, usually formed by nine microtubule triplets arranged radially, which recruit and organize the pericentriolar matrix (1)(2)(3).…”
Section: Introduction: the Centrosome -An Organizing Center Of Multipmentioning
confidence: 99%